Komunikasi Digital Berbasis Nilai: Studi tentang Peran Mahasiswa Program Studi Manajemen Angkatan 2023 Universitas Muhammadiyah Bandung sebagai Mobile Citizen dan Mobile Beacon di Era Media Sosial - Lanina Pratiwi; Muhammad Zaki; Nuri Triani Anggraeni; Sofa Parihah Nurasiah (Indo Publishing, 2026)
The rapid development of digital technology has transformed communication patterns, particularly through the use of social media as a platform for information sharing and interaction. This phenomenon requires university students not only to possess digital literacy skills but also to apply ethical principles in digital communication. This study aims to analyze the role of Management Study Program students from the Class of 2023 at Universitas Muhammadiyah Bandung as mobile citizens and mobile beacons in the era of social media. The study employed a quantitative approach using a descriptive survey method. Data were collected through questionnaires distributed to 87 respondents selected using the proportionate stratified random sampling technique. The findings indicate that most students demonstrate responsible digital communication practices by verifying information before sharing it, applying the principle of tabayyun, utilizing digital technology for self-development, and contributing to a positive digital environment through the dissemination of educational and Islamic values-based content. However, the use of social media to support academic activities still requires further optimization. The findings suggest that the internalization of Islamic values contributes to shaping students into critical, ethical, and responsible digital citizens.